Level of Awareness about Osteoporosis among Women 50 Years and Older in Puerto Rico - Monsanto, Homero A. (Puerto Rico Health Sciences Journal, 2010)
Osteoporosis is an established and well-defined disease that affects millions of people around the world and is a major cause of morbidity. Not much is known about the level of awareness of the condition among the general population in Puerto Rico. The objectives of this study were: 1) to determine the level of awareness and knowledge about osteoporosis among women 50 years and older in Puerto Rico, and 2) to describe the differences in level of awareness and knowledge among women who have been diagnosed with osteoporosis and those who have not. Telephone interviews were conducted among a sample of women 50 years and older who were residents of Puerto Rico during the month on February, 2005. A four-page questionnaire was developed to address the study objectives. Of the total number of women contacted (342), 28 (8%) indicated they did not know anything about osteoporosis and could not answer the remainder of the questionnaire. In spite of widespread awareness about the condition, more than one in ten women responded they did not know what factors contribute to the development of osteoporosis and nearly one in five women did not know the complications associated with osteoporosis. Public education campaigns must address risk factors and the strategies to overcome those that are modifiable in order to prevent the development of osteoporosis and its complications. [P R Health Sci J 2010;1:54-59]